2020
DOI: 10.1007/s10955-020-02537-9
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization in a One-Dimensional Periodic Landscape

Abstract: We consider the crystallization problem for a finite one-dimensional collection of identical hard spheres in a periodic energy landscape. This issue arises in connection with the investigation of crystalline states of ionic dimers, as well as in epitaxial growth on a crystalline substrate in presence of lattice mismatch. Depending on the commensurability of the radius of the sphere and the period of the landscape, we discuss the possible emergence of crystallized states. In particular, we prove that crystalliz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Brascamp and Lieb [11] as well as Aizenman and Martin [1] gave important results on the optimality of the equidistant configuration concerning the Jellium model, see also [31]. The emergence of crystallized state for one-dimensional system embedded in a periodic energy landscape is furthermore studied in [18] by Friedrich and Stefanelli where it is shown that equidistant ground states are generally not expected. Furthermore, Blanc and Le Bris [9] proved the periodicity of the ground state for the one-dimensional Thomas-Fermi-von-Weizsäcker energy.…”
Section: Introductionmentioning
confidence: 99%
“…Brascamp and Lieb [11] as well as Aizenman and Martin [1] gave important results on the optimality of the equidistant configuration concerning the Jellium model, see also [31]. The emergence of crystallized state for one-dimensional system embedded in a periodic energy landscape is furthermore studied in [18] by Friedrich and Stefanelli where it is shown that equidistant ground states are generally not expected. Furthermore, Blanc and Le Bris [9] proved the periodicity of the ground state for the one-dimensional Thomas-Fermi-von-Weizsäcker energy.…”
Section: Introductionmentioning
confidence: 99%
“…Recent results for positive temperature including an analysis of boundary layers are obtained in [34,35]. For results on dimers we refer to [6,29].) The first rigorous results for a two-dimensional system were achieved in [32,33,43]; see also the recent paper [18].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical behaviour of one-dimensional systems has been of interest for decades. Such systems serve as toy models for higher-dimensional theoretical investigations and are of interest with respect to one-dimensional structures, see, e.g., [7,8,10,11,19]. In order to understand the effective behaviour of materials, the systems are studied as the number of particles tends to infinity.…”
Section: Introductionmentioning
confidence: 99%